2015
DOI: 10.1016/j.celrep.2015.01.052
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Signaling Network Temporally Resolves Specific versus Promiscuous Phosphorylation

Abstract: If specific and functional kinase- or phosphatase-substrate interactions are optimized for binding compared to promiscuous interactions, then changes in phosphorylation should occur faster on functional versus promiscuous substrates. To test this hypothesis, we designed a high temporal resolution global phosphoproteomics protocol to study the high-osmolarity glycerol (HOG) response in the budding yeast Saccharomyces cerevisiae. The method provides accurate, stimulus-specific measurement of phosphoproteome chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(143 citation statements)
references
References 65 publications
8
127
0
Order By: Relevance
“…Phosphorylation of the MAPK consensus sites in the Ste50 IDR results in attenuation of signaling by dissociation of the signaling complex from the membrane (33). Phosphoproteomic studies also indicate phosphorylation of a subset of these sites in standard growth conditions (19,(38)(39)(40)(41)(42)(43), which we refer to as basal phosphorylation. To test the function of this region in S. cerevisiae, we therefore made an unphosphorylatable mutant, where each consensus site was mutated to alanine (referred to as 5A mutant) (Materials and Methods).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of the MAPK consensus sites in the Ste50 IDR results in attenuation of signaling by dissociation of the signaling complex from the membrane (33). Phosphoproteomic studies also indicate phosphorylation of a subset of these sites in standard growth conditions (19,(38)(39)(40)(41)(42)(43), which we refer to as basal phosphorylation. To test the function of this region in S. cerevisiae, we therefore made an unphosphorylatable mutant, where each consensus site was mutated to alanine (referred to as 5A mutant) (Materials and Methods).…”
Section: Significancementioning
confidence: 99%
“…We calculated the basal net charge of each IDR by considering its net charge (sum of positive and negatively charged residues) including basal phosphorylation at up to two SP sites, as mass spectrometry studies have found that up to two serines are phosphorylated in this IDR under basal conditions in S. cerevisiae (as reported in refs. 19,[38][39][40][41][42][43]. Therefore, if the IDR has two or more SP sites, we assume that two of these serines are phosphorylated under basal conditions and add a charge of -4 (-2 for each phosphorylation site) to the net charge of the IDR (see Materials and Methods for details).…”
Section: Basal Net Charge Of Diverged Sequences Is Correlated With Fumentioning
confidence: 99%
“…http://dx.doi.org/10.1101/209676 doi: bioRxiv preprint first posted online response to NaCl, an osmotic stressor, measuring phosphorylation changes for 60 seconds poststimulation at uniform 5 second intervals (Kanshin et al, 2015). They identified 1,596 phosphorylated proteins, including 1,401 dynamic phosphopeptides on 784 proteins based on their fold changes in the salt stress time series with respect to a control (Table S13).…”
Section: Tps Generates High-quality Pathway Models From Lower Temporamentioning
confidence: 99%
“…As proteomic technologies continue to improve in terms of depth of coverage Zhou et al, 2013) and temporal resolution (Humphrey et al, 2015;Kanshin et al, 2015;Reddy et al, 2016), the need to systematically interpret these data will likewise grow. TPS enables reasoning with temporal phosphorylation changes and physical protein interactions to define what drives the vast protein modifications that are not represented by existing knowledge in pathway databases.…”
Section: Future Directions In Pathway Synthesismentioning
confidence: 99%
See 1 more Smart Citation